Fra poiêsis til duddjot: Om handlingsbåren kunnskap og rematriering av duodji - Jernsletten, Jorunn (Tidsskrift for kulturforskning, 2024)
What does it mean to recreate a museum object that has gone out of use and is no longer produced? What kind of knowledge needs to be recreated? Production of traditional craft products is intangible cultural heritage. It relies on knowledge that is recreated every time it is used, which cannot be passed on without the action to which it is linked. The term action-based knowledge is used to denote this process but is also generally used for bodily-based knowledge. This obscures the distinctiveness of the knowledge required to produce objects. Aristotle’s term poiesis denoted the production process itself. In our time, it has slipped into the concept of practice, so that the distinction between different types of actions have been blurred. In the museums, old objects are still found and processes of recreating them are used in decolonization. Thus, knowledge traditions that were broken due to forced assimilation are resumed. Working with intangible traditions makes it clear that this type of knowledge is something you do, not something you have. The Northern Sami verb duddjot describes the production of duodji, Sámi crafts. Embedded in this activity are both poiesis and practice, and from a scientific perspective also episteme, in the form of productive understanding. Through duddjot, you transform a material into an object while transforming yourself by expanding your own expertise so that it overlaps with other craftsmen in the present, past and future. Thus, you convey both technical knowledge and values.